Across the great divide : between analytic and continental political theory - Arnold, Jeremy, 1980- (Stanford University Press, 2020)
"Arguing that debates over legitimacy, political violence, freedom, and justice would benefit greatly from cross-tradition theorizing, this book shows how putting analytic and continental political theory in conversation would help us to overcome these intractable problems"--